Peran Pengelolaan Dokumen Administrasi Ekspor Impor Pada Perusahaan Jasa Kepabeanan PT Kargo Trans Solusi - Jessie Aprillia Setiawan; Siti Ning Farida (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Internship activities are a way of applying academic learning to the world of work with the aim of providing work experience to students. This article discusses practical internship activities carried out at PT. Kargo Trans Solusi, a customs services company that focuses on export-import document administration. The aim of this internship is to gain an understanding of the role of administration in international trade, especially in managing customs documents such as Goods Export Notifications (PEB) and Goods Import Notifications (PIB). To find out about the management of export-import administration documents at PT. Kargo Trans Solusi, this research uses a qualitative approach with a case study method.